Partial characterization of a cell proliferation-inhibiting protein produced by Helicobacter pylori. - Knipp, U (1996)
Despite the induction of an immunological reaction, Helicobacter pylori-associated gastritis is a chronic disease, suggesting that this microbe can evade the host immune defense. Previous studies by our group showed that H. pylori suppresses the in vitro proliferative response of human mononuclear cells to mitogens and antigens. Here we demonstrate that the antiproliferative activity of H. pylori also affects the proliferation of various mammalian cell lines (U937, Jurkat, AGS, Kato-3, HEP-2, and P388D1). This effect is detectable in the first 16 h of incubation and maximal between 24 and 48 h. In addition, the presence of H. pylori significantly diminished the protein synthesis of cells in the first 6 h of incubation, comparable to the results with cycloheximide and diphtheria toxin. The urease enzyme, the cagA gene product, and the vacuolizing cytotoxin of H. pylori were excluded as causative agents of the antiproliferative effect by using isogenic knockout mutant strains. The inhibitory effect was not due to a lytic activity of this bacterium. The results reported here indicate that the responsible factor is a protein with an apparent native molecular mass of 100 +/- 10 kDa. Our work implicates the presence of a protein factor in H. pylori (termed PIP [for proliferation-inhibiting protein]) with antiproliferative activity for mammalian cells, including immunocompetent and epithelial cells. Thus, it is reasonable to presume that this property may contribute to the pathogenesis of H. pylori-induced diseases. It may be involved on the one hand in immune response evasion and on the other hand in the suppression of epithelial repair mechanisms.